Determining short-lived solid forms during phase transformations using molecular dynamics. Issue 27 (10th June 2019) - Larsen, Anders S.; Olsen, Mark A.; Moustafa, Hadeel; Larsen, Flemming H.; Sauer, Stephan P. A.; Rantanen, Jukka; Madsen, Anders Ø.
Abstract : We demonstrate that elusive high-energy metastable crystal structures can be determined from molecular dynamics simulations. Abstract : The dehydration process of the widely studied drug theophylline is unravelled by combining molecular dynamics simulations with powder X-ray diffraction and solid-state NMR measurements and calculations. Based on the simulation, we determine a high-energy short-lived metastable crystal form, and additionally suggest the existence of a fast-converting form.